Gazzâli ve David Hume Bilgi Kuramlarında Dinî Bilginin İmkânı/ The Possibility of Religious Knowledge in al-Ghazzali and David Hume’s Theory of Knowledge - Yıldız, Mustafa (Journal of History Culture and Art Research, 2015)
The Possibility of Religious Knowledge in al-Ghazzali and David Hume’s Theory of Knowledge Abstract This paper compares the possibility of religious knowledge in the theory of knowledge of al-Ghazzali and David Hume. The purpose of the article is that basing these philosophers’ religious knowledge in their theory of knowledge. According to al-Ghazzali, it can be used one of the three ways in a theory of knowledge, for a basis of religious belief. First is basing religious beliefs by relying on reports of the prophets without making a rational inquiry. Second is basing religious beliefs by knowledge, which is gained by reasoning. Third is spiritual intuition obtained by religious practice. David Hume argued that believing reports of the prophets relies on miracles that are not that a reliable source of information. He also argued that religious beliefs cannot rely on reasoning method. According to him doing such a thing is beyond the limits of the powers of reason. Also, it is impossible to rely religious belief on spiritual intuition in Hume’s theory of knowledge. Because, human being doesn’t have spirit in this meaning. According to him, roots of religious belief in human nature is based on some feelings. These feelings are like such as fear and hope, which humans feel against unknown natural events. Gazzâli ve David Hume Bilgi Kuramlarında Dinî Bilginin İmkânı Öz Bu makale Gazzâlî ve David Hume bilgi kuramlarında dinî bilginin imkânını karşılaştırmaktadır. Bunu yapmadaki amacı her iki düşünürün ortaya koydukları bilgi kuramlarında dinî bilgi için nasıl bir temel öngördüklerini ortaya koymaktır. Gazzâlî’ye göre, bir bilgi kuramında üç yoldan birinin kullanılmasıyla dinî inanca bir temel bulanabilir. Bunlardan birincisi, dinî inançların aklî bir açıklaması yapılmaksızın peygamberlerden nakledilen haberlere güvenmek suretiyle inancın temellendirilmesidir. İkincisi, istidlal yöntemiyle ulaştığımız bilgilerin inancımızı temellendirmesidir. Üçüncüsü, dinî pratiklerle elde edilen ruhsal sezginin dinî inanca temel olabilmesidir. David Hume peygamberlerden nakledilen haberlere güvenmenin mucizeye dayandığını, mucizenin ise güvenilir bir bilgi kaynağı olmadığını ileri sürdü. İstidlal yöntemiyle de dinî inancın temellendirilemeyeceğini ileri sürdü. Ona göre böyle bir şeyi yapmak aklın yetki sınırlarının dışındadır. Hume’un bilgi teorisinde ruhsal bir sezgi ile dinî inançları temellendirmek de mümkün değildir. Çünkü ona göre insanın bu anlamda bir ruhu yoktur. Ona göre dinî inançların insan doğasındaki kökenleri bazı duygulara dayanmaktadır. Bunlar da bilinmez tabiat olaylarına karşı insanın hissettiği korku ve umut gibi duygulardır.